INTEGRASI PENDIDIKAN AGAMA DAN SAINS DALAM AL-QUR’AN DAN HADIST: MODEL HOLISTIK MENUJU PEMBENTUKAN ULUL ALBAB DI ERA DIGITAL - Rasti Astuti Laisaan; Hittotun Nahdiyah; Alfin Nuris Sa’adah; Saida Munawaroh; Abdurrahman Abdurrahman (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study examines the integration of Islamic religious education and science from the perspective of the Qur'an and Hadith. The separation between these two fields of knowledge has led to an epistemological crisis that has weakened the spiritual dimension amidst modern technological advances. Using a library research approach and content analysis, this study explores the philosophical, theological, and practical foundations of this integration effort. The findings indicate that the Qur'an and Hadith consistently encourage humans to think critically, observe the universe, and connect empirical phenomena with the values ??of monotheism. Therefore, the integration of religious education and science is imperative to realize a learning system that harmonizes intellectual and spiritual intelligence. The results of this study emphasize the urgency of developing a monotheism-based Islamic science curriculum as a response to the moral, ethical, and technological challenges of the contemporary era.